Early Child Marriage in India for the Sake of Tradition or an ‘Unconscious’ Organized Crime - Fitri Rofiyarti (MOTORIC, 2018)
The number of cases occurring in India proves that there has been a cultural shift being a crime case, the marriage of children is similar to a practice who has similarities with slavery. According to UNICEF's State of the World's Children 2009, underage marriage has many negative implications, including the fact that pregnancy at an immature age (women 15-19 years old) leads to death in children. Although the child can survive, there will be many nutritional problems and cognitive abilities. In this study the authors wanted to know what under the circumstances of the marriages that occur in India at this time is still a manifestation of the continuity of cultural values ??or an organized crime in line with the number of cases with the negative impacts that occur. In addition, the author will link the marriage of minors with the extent to which globalization also contributes to the problem. The author sees that there has been a crime in childhood marriage in India. Globalization makes this issue an international issue so that it can be made to fight it globally Keywords: Early Child Marriage, India, Tradition, Impact